2015 IEEE Security and Privacy Workshops 2015
DOI: 10.1109/spw.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Privacy and Direct-to-Consumer Genetics: Big Consumer Genetic Data -- What's in that Contract?

Abstract: This is a brief position paper providing a summary of current research on the legal regulation of Direct-to-Consumer Genetic Testing (DTCGT), focussing on the contracts used by DTCGT companies. The overall aim of the larger project has been to explore the existing legal mechanims for the protection of the rights of consumers in their sequenced genetic data in the context of DTCGT. There are several areas of law which could be drawn upon to regulate the industry or which may have relevance for the protection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In 2002, as part of research aiming at identifying the availability of DTC GT, Gollust et al identified 14 companies selling health-related DTC GT [5]. A recent study by Phillips (2015) revealed that the market of health-related DTC GT has grown significantly in the last decade reaching over 100 companies [6]. Considering that these searchers were performed in English, the total number of companies offering DTC GT may be assumed to be even larger.…”
Section: Current Offer Of Dtc Gt -Expanded Scope Audience and New Tementioning
confidence: 99%
See 1 more Smart Citation
“…In 2002, as part of research aiming at identifying the availability of DTC GT, Gollust et al identified 14 companies selling health-related DTC GT [5]. A recent study by Phillips (2015) revealed that the market of health-related DTC GT has grown significantly in the last decade reaching over 100 companies [6]. Considering that these searchers were performed in English, the total number of companies offering DTC GT may be assumed to be even larger.…”
Section: Current Offer Of Dtc Gt -Expanded Scope Audience and New Tementioning
confidence: 99%
“…Furthermore, the web-based interpretation services can provide health-related information on the basic of raw data received in ancestry genetic testing, which is discussed in the following sections of this article. (2015) revealed that the market of health-related DTC GT has grown significantly in the last decade reaching over 100 companies [6]. Considering that these searchers were performed in English, the total number of companies offering DTC GT may be assumed to be even larger.…”
mentioning
confidence: 99%
“…Several researchers have discussed the potential privacy and security risks associated with DTC genetic testing such as the possibility of re-identification of de-identified DNA data and lack of clarity in privacy policies of companies in how DNA samples and data will be handled [31][36] [40]. Sharing of DNA data with pharmaceutical organizations [14] and law enforcement [29] [47] has raised concerns about privacy risks for consumers.…”
Section: Privacy Concerns About Dtc Genetic Testingmentioning
confidence: 99%
“…Genome data privacy has thus been a concern in both research 3.5. Public genomes and follow-up research and commercial contexts [Nature, 2013, Phillips, 2015, and controlledaccess sharing for genome data research is common (e.g. as performed by the United States Database of Genotypes and Phenotypes, dbGaP), while commercial groups often promise privacy for individual-level genetic data.…”
Section: Genomic Data Privacy and Accessmentioning
confidence: 99%